2005
DOI: 10.1007/s00192-005-0011-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the long-term success of periurethral collagen therapy in the office

Abstract: Prior anti-incontinence surgery was the one factor analyzed that showed a trend toward this long lasting success. No other factors were predictive of negative stress tests for over 1 year. Prior anti-incontinence surgery seems to represent a factor involved in the long-term success of periurethral bulking in the office with glutaraldehyde crosslinked bovine collagen for the treatment of urodynamic stress incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…In a study with 184 female patients where collagen was used as the periurethral injection material [22], similar to our study, it is reported that the previous anti-incontinence treatment is an important factor contributing to the success of the treatment in the patients who had been reported 'cure' for more than one year after the injection. In this study, analyzing the affects of obesity, menopausal status, hormonal treatment and the type of the incontinence on the results, it was ascertained that they did not make a significant difference [22]. Even though the affects of obesity and post-menopausal status on the development of SUI in females is very well known, and their significance in the prediction of the success of the surgeries was researched in many studies, the affects of these factors in the results of transurethral injection treatment are not known very well.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In a study with 184 female patients where collagen was used as the periurethral injection material [22], similar to our study, it is reported that the previous anti-incontinence treatment is an important factor contributing to the success of the treatment in the patients who had been reported 'cure' for more than one year after the injection. In this study, analyzing the affects of obesity, menopausal status, hormonal treatment and the type of the incontinence on the results, it was ascertained that they did not make a significant difference [22]. Even though the affects of obesity and post-menopausal status on the development of SUI in females is very well known, and their significance in the prediction of the success of the surgeries was researched in many studies, the affects of these factors in the results of transurethral injection treatment are not known very well.…”
Section: Discussionsupporting
confidence: 86%
“…After an 18 month follow-up, 398 patients were evaluated, and it was demonstrated that BMI did not have any affect on the surgery result, while menopausal status and age were found to be independent risk factors decreasing the success of the sling procedures [21]. In a study with 184 female patients where collagen was used as the periurethral injection material [22], similar to our study, it is reported that the previous anti-incontinence treatment is an important factor contributing to the success of the treatment in the patients who had been reported 'cure' for more than one year after the injection. In this study, analyzing the affects of obesity, menopausal status, hormonal treatment and the type of the incontinence on the results, it was ascertained that they did not make a significant difference [22].…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates a potential benefit in the elderly and in women with recurrent or persistent incontinence after previous surgery. Koduri et al [46] also found that previous anti-incontinence surgery was the one factor that showed a trend for negative stress tests over a year after injection [46]. Additionally, as it carries a low risk of long-term urinary retention and de novo urinary storage symptoms, some authors have suggested that injectable therapy may have a role in women at increased risk for these postoperative sequelae.…”
Section: Morbidity Of Injectable Therapymentioning
confidence: 95%
“…30 One RCT compared collagen injections to open surgery (fascial sling, Burch, or needle suspension) for SUI in 133 women. 13 At 1 year, 32.8% of patients were not satisfied with their procedure compared with 20.4% in the open surgery group.…”
Section: Collagen (3 Rcts)mentioning
confidence: 99%